2020
DOI: 10.21037/cdt.2019.10.07
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatic heart disease: current status of diagnosis and therapy

Abstract: Rheumatic heart disease (RHD) is the only preventable cardiovascular disease which causes significant morbidity and mortality particularly in low-and middle-income countries. Early clinical diagnosis is key, the updated Jones criteria increases the likelihood of diagnosis in endemic settings, including the echo diagnosis of sub-clinical carditis, polyarthralgia and monoarthritis as well as amended thresholds of minor criteria. The mainstay of rheumatic heart valve disease (RHVD) is a thorough clinical and echo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 67 publications
2
24
0
5
Order By: Relevance
“…Rheumatic coronary illness (RHD) being the prevailing type of valvular heart disease in under-developed countries [6]. Acute rheumatic fever and rheumatic heart disease are thought to be the outcome of an autoimmune response, but the precise pathogenesis remains unclear [7]. In this study, out of fifty patients, the majority of study subjects were in the age group of 20-29 years, with a female preponderance of 64% while the mean age was 33.71±6.82 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rheumatic coronary illness (RHD) being the prevailing type of valvular heart disease in under-developed countries [6]. Acute rheumatic fever and rheumatic heart disease are thought to be the outcome of an autoimmune response, but the precise pathogenesis remains unclear [7]. In this study, out of fifty patients, the majority of study subjects were in the age group of 20-29 years, with a female preponderance of 64% while the mean age was 33.71±6.82 years.…”
Section: Discussionmentioning
confidence: 99%
“…Sani MU et al reported pulmonary hypertension (72.1%) in individuals with rheumatic heart disease [19]. The data suggest that recurrences of RF are higher in patients with RHD and each recurring disease episode further damages the heart [20]. The monitoring of medical therapy because RHD at this stage would warrant lifelong prophylaxis while in order to counter these recurrent attacks effective secondary prevention is required, which relies on accurate case detection for the appropriate use of prophylactic antibiotics and regular medical surveillance whereas the echocardiography plays an important role firstly, in early detection of RHD [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Echocardiographic Diagnostic Criteria based on the 2012 World Heart Federation for RHD is categorized into 2 based on age(< 20 years and > 20 years of age). In echocardiographic criteria for paediatric's less than or equal to 20 years is divided into 3 sections definite, borderline and normal echocardiographic findings [12,13] is shown in Table 2. [12,13] is shown in Table 3.…”
Section: Laboratory Testmentioning
confidence: 99%
“…Rheumatic heart disease (RHD) remains a number one cause of preventable cardiovascular diseases (CVDS) [ 1 ]. It is also the major cause of heart disease for children and teenagers in low and middle-income countries and several marginalized groups in developed countries, causing a major health challenge for them [ 2 ].…”
Section: Introductionmentioning
confidence: 99%